Biliary stenting alone versus biliary stenting combined with 125I particles intracavitary irradiation for the treatment of advanced cholangiocarcinoma - Qing Pang (Nature Portfolio, 2019)
Abstract We aimed to compare the efficacy of percutaneous transhepatic biliary stenting (PTBS) and PTBS combined with 125I particles implantation in the treatment of advanced extrahepatic cholangiocarcinoma (EHC). A total of 184 advanced EHC patients, who received PTBS (PTBS group) or PTBS combined with 125I particles implantation (PTBS + 125I group) from January 2012 to April 2017 in our department, were retrospectively reviewed. The improvement of jaundice and liver function was observed in both groups. The postoperative complications, risk of biliary re-obstruction, and overall survival (OS) were compared between the two groups. Amongst, 71 cases received PTBS and 113 had the additional implantation of 125I particles. The jaundice and liver function were significantly improved in all patients, especially in PTBS + 125I group. There was no significant difference in the risk of postoperative complications between the two groups. However, the risk of biliary re-obstruction significantly reduced in PTBS + 125I group (19.5% vs. 35.2%, p = 0.017). Kaplan Meier analysis showed that patients in PTBS + 125I group had a significantly better OS, both for hilar and distal cholangiocarcinoma. Univariate analysis demonstrated that preoperative levels of carbohydrate antigen 19-9 (CA19-9), total bilirubin, neutrophil count, lymphocyte count, and different therapeutic method were significant factors affecting OS. Multivariate analysis further identified the treatment of PTBS combined with 125I particles implantation as an independent protective prognostic factor (HR = 0.26, 95% CI: 0.17–0.39, p < 0.001). In conclusion, for patients with advanced EHC, PTBS combined with 125I particles implantation is superior to PTBS alone in improving liver function, inhibiting biliary re-obstruction, and prolonging survival time.